Evaluation of 35 Cases of Abdominal Lymphoma - Rashid, MM; Rahman, MM; Rabbi, AA; Talukder, SI (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 170-176 The abstract of this article is available on the PubMed website